IBM z/OS V2R2 JES2, JES3, and SDSF - Winnard, Keith (IBM Corporation, International Technical Support Organization, 2015)
This IBM Redbooks publication helps you to become familiar with the technical changes that were introduced into the JES2 JES3, and SDSF areas with IBM z/OS V2R2. Changes include: JES2 updates that are related to z/OS V2R2, JES2 updates that are related to z/OS V2R2, and changes in SDSF in z/OS V2R2. --
Number on resource description page: SG24828700. - "Z Systems.". - Includes bibliographical references. - Online resource; title from cover page (Safari, viewed January 21, 2016)
Keywords: z/OS; Database management; Information storage and retrieval systems; Information Systems; Bases de données; Gestion; Systèmes d'information